The costimulatory activity of the CD26 antigen requires dipeptidyl peptidase IV enzymatic activity. - Tanaka, T (1993)
T cells have been shown to express CD26, a known ectoenzyme with dipeptidyl peptidase IV (DPPIV; EC 3.4.14.5) activity in its extracellular domain. CD26 can also deliver a second costimulatory signal and contribute to T-cell activation. In an earlier study, we established CD26-transfected Jurkat T-cell lines and demonstrated that monoclonal antibody-mediated crosslinking of CD26 and CD3 induced interleukin 2 (IL-2) production. To determine the contribution of DPPIV enzymatic activity to the costimulatory activity of CD26, human CD26 cDNA was mutated so that active-site serine was replaced by alanine. The mutant CD26 antigen lacked DPPIV enzyme activity but still retained reactivity with three anti-CD26 monoclonal antibodies directed against distinct epitopes of CD26. After stimulation with a combination of anti-CD26 and anti-CD3 antibodies, wild-type CD26 (DPPIV+)-transfected Jurkat cells produced substantially more IL-2 than did mutant CD26 (DPPIV-) or CD26- control transfectants. Nevertheless, the mutant CD26-transfected cells still produced significantly more IL-2 than did CD26- control transfectants. These results suggest that DPPIV activity plays an important but not absolute role in the co-stimulatory activity of CD26 in this system. We also found that wild-type CD26 (DPPIV+) transfectants produced more IL-2 than mutant CD26 (DPPIV-)-transfected cells or CD26- control transfectants when triggered by stimuli not involving CD26, such as anti-CD3 and phorbol ester. These results suggest that the DPPIV activity of CD26 functions to augment the cellular responses of CD26-transfected Jurkat cells to external stimuli mediated by CD26 and/or the CD3/T-cell receptor complex, thus enhancing IL-2 production.